THE ROLE OF EXPORT POLICIES AND ENVIRONMENTAL CONSERVATION IN POVERTY REDUCTION IN INDONESIA WITHIN THE FRAMEWORK OF THE SDGS - Sari, Cut Putri Mellita; Nailufar, Fanny; Trisniarti, Noviami; Yunita, Nur Afni (LPPM Universitas Malikussaleh, 2025)
This study analyzes the role of export policies and environmental conservation in poverty reduction in Indonesia within the framework of the Sustainable Development Goals (SDGs). The main focus is directed towards palm oil exports as a proxy for export policy and the area of reforestation as a proxy for environmental conservation efforts, with the number of poor people as the dependent variable. This study uses time series data from 2000–2023 and a linear-log regression approach. The research finds that an increase in palm oil export volume significantly reduces the number of poor people, affirming the role of the strategic export sector in supporting overall economic growth. On the contrary, reforestation shows a positive relationship with the number of poor people, indicating that conservation policies have not yet fully responded to the social and community welfare dimensions. The R² test result of 82.12% indicates that the model has a strong explanatory power. This research recommends a synergy between economic and environmental policies in an integrated manner so that poverty alleviation efforts align with ecosystem protection and local community empowerment.